USING DICTATION TECHNIQUE IN TEACHING ENGLISH LISTENING SKILL AT ELEVEN GRADE OF MAN 3 KOTA PEKANBARU - Iffatunniswa, Iffatunniswa; Nuardi, Nuardi (State Islamic University of Sultan Syarif Kasim Riau, 2025)
This study investigates the use of the dictation technique in improving English listening skills among eleventh-grade students at MAN 3 Kota Pekanbaru. Employing a quantitative pre-experimental design, the researcher administered pre- and post-tests to 36 students to measure the effect of dictation. The findings reveal a significant improvement in listening ability, with the mean score increasing from 52.64 to 74.03. A paired-sample t-test indicated a statistically significant difference (p = 0.000), affirming that dictation effectively enhances students’ listening skills. The study recommends that teachers incorporate dictation as a practical method to support listening comprehension.